2009
DOI: 10.1007/s00122-009-1244-6
|View full text |Cite
|
Sign up to set email alerts
|

A single recessive gene controls cadmium translocation in the cadmium hyperaccumulating rice cultivar Cho-Ko-Koku

Abstract: The heavy metal cadmium (Cd) is highly toxic to humans and can enter food chains from contaminated crop fields. Understanding the molecular mechanisms of Cd accumulation in crop species will aid production of safe Cd-free food. Here, we identified a single recessive gene that allowed higher Cd translocation in rice, and also determined the chromosomal location of the gene. The Cd hyperaccumulator rice variety Cho-Ko-Koku showed 3.5-fold greater Cd translocation than the no-accumulating variety Akita 63 under h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 22 publications
2
67
1
Order By: Relevance
“…Physiological studies indicate that Choko-koku, Anjana Dhan, and Jarjan are characterized by a common Cd-transport process that enables an extremely high amount of Cd translocation from roots to shoots (Tezuka et al 2010, Ueno et al 2009, Uraguchi et al 2009). QTL analyses, including ours, identified major QTLs responsible for the high-Cd trait of these three cultivars in almost identical regions on chromosome 7 (Tezuka et al 2010, Ueno et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Physiological studies indicate that Choko-koku, Anjana Dhan, and Jarjan are characterized by a common Cd-transport process that enables an extremely high amount of Cd translocation from roots to shoots (Tezuka et al 2010, Ueno et al 2009, Uraguchi et al 2009). QTL analyses, including ours, identified major QTLs responsible for the high-Cd trait of these three cultivars in almost identical regions on chromosome 7 (Tezuka et al 2010, Ueno et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies indicate that Choko-koku, Anjana Dhan, and Jarjan are characterized by a common Cd-transport process that enables an extremely high amount of Cd translocation from roots to shoots (Tezuka et al 2010, Ueno et al 2009, Uraguchi et al 2009). QTL analyses, including ours, identified major QTLs responsible for the high-Cd trait of these three cultivars in almost identical regions on chromosome 7 (Tezuka et al 2010, Ueno et al 2009). Very recently, it has been revealed that OsHMA3, a P 1B -type ATPase, is encoded by a gene within the QTL region on chromosome 7 and plays an important role in controlling shoot Cd accumulation in rice (Miyadate et al 2011, Ueno et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19] The gene responsible for the QTL effect has been identified as OsHMA3 in the Cho-kokoku and Anjana Dhan cultivars, 20,21 but the gene in Habataki has not yet been identified. The amino acid at position 80 in OsHMA3 is critical for its transport Proposed model for the role of OsNramP1 in cd translocation from the root to the shoot.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%